TIPOLOGI PERUBAHAN WUJUD ARSITEKTUR PAMESUAN DI DESA BONGKASA PERTIWI, KABUPATEN BADUNG - I Gede Gandhi Silantara (Jurnal Teknik Gradien, 2023)
Architectural development is a manifestation of human desire for a better direction. If observed, its development can resutl in changes to the architectural from itself. This change is a product of adaptation or response to developments in culture, economy, environtmeent, technology and architectural styles. One example that can be observed is the change in pamesuan architecture int he traditional village of Badung Regency. This study aims to identify and analyze the typology of change in the form of pamesuan architecture in Bongkasa Pertiwi Village, Badung Regency. The research method used in this study is a qualitative method, with data analysis in the form of descriptive originating from empirical information. The analysis process is based on the form and general function of the pamesuan based on theoretical studies as a grand concept. The results of identification and grouping, there are four types of architectural forms of pamesuan in Bongkasa Pertiwi Village. Each type has several differences such as the type, structure, material, appearance concept and dimensions. The results of the grouping are then analyzed based on theoretical studies to find change in from that have occured. Changes in form were found in the form of addition, elimination and movement of shapes and elements such as the addition of lighting elements, dimensions of the entrance. elimination of elements forming the tri angga concept, namely the roof (head). Movement of the form of circulation access in the form of a ramp. Changes are certainly good, but still pay attention to the core elements and characteristics of the pamesuan architecture in each region. This research is expected to provide benefits in exploring local wisdom in traditional Balinese architecture, especially pamesuan architecture.